USING GRAMMAR IN ASSESSING ACADEMIC WRITING: A NARRATIVE STUDY OF EFL STUDENT EXPERIENCES - ., Sam Hermansyah; Aksan, Muhammad; Isumarni, Isumarni; Nur hikmah, Nur hikmah; Faradillah, Nurul (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
Advances in technology have made it easy for all writers to check their academic writing using automated writing assessment programs. However, using this program can have both advantages and disadvantages. Therefore, its advantages and disadvantages should be considered. To address this need, this study aimed to identify the strengths and weaknesses of the Grammarly program as an automated writing assessment program for assessing academic writing. Using narrative research to explore the experiences of three Indonesian graduate students through interviews and documents, the program offers helpful color-coded feedback with explanations and examples, easy account access, rapid assessment speed, and It was indicated that they provide free services for academic evaluation. write. However, we have identified several concerns when using this program, including: Weaknesses of the program included some misleading feedback, weaknesses in English type recognition and reference lists, and lack of context and content assessment. Further research is needed on the effectiveness of the feedback provided by Grammarly in improving the quality of students' writing.